Majâz Dalam Pandangan Abd Al-Qahir Al-Jurjani - M. Muizzuddin (Jurusan Pendidikan Bahasa Arab Fakultas Tarbiyah dan Keguruan Institut Agama Islam Negeri Sultan Maulana Hasanuddin, 2021)
The development of balaghah as a field of Arabic studies cannot be separated from the study of the i'jaz al-Qur'an itself. It was started by Abu Ubaidah Mu'ammar Ibn al-Matsna (W. 210H) who wrote the book titled Majầz al-Qur’ần. The word majầz is the first study to be used in the history of balaghah studies. This study is very related to the discipline of balaghah which includes al-Bay'n, al-Ma'ầni, and Badi ’, even sharf science and nahwu science. The objectives of this study are: (1) to know the biography of Abdul Qahir al-Jurjani and the history of his thoughts about asrầr balầghah; revealed the majầz theory in asrầr balầghah according to Abdul Qầhir al-Jurjầni along with examples in the Qur'ān. This research uses descriptive analytic qualitative with literature review literature. The results of the study are: (1) Abdul Q -hir al-Jurjầni an expert balầghah in the study of asrầr balầghah elaborates in detail about the concept of maj (z, (2) The concept of majầz describes the Metaphor (isti'ầrah), Comparative Art (tasybὶh), Parable (matsal) ), equation (tamtsil).